Susceptibility Weighted Imaging in Migraines with and Without Aura: A Case-Control Study - Scutelnic, Adrian; Klail, Tomas; Moor, Diego; Slavova, Nedelina; Petroulia, Valentina; Jung, Simon; Branca, Mattia; Fischer, Urs; Riederer, Franz; Wiest, Roland; Schankin, Christoph J (Neurology international, 2025)
The asymmetry of cortical veins in susceptibility weighted imaging (SWI) in MRI might be a biomarker for migraine auras and cortical spreading depression (CSD). The aim of this study was to assess in humans if SWI asymmetry can be found in patients who have migraine attacks without auras. We included patients ( = 100 per group) from the emergency room setting when they (i) presented with an acute neurological deficit or headache; (ii) had a discharge diagnosis of a migraine aura, a migraine without an aura, or neither (controls without stroke or epilepsy); and (iii) had a brain MRI with SWI in the acute setting. In the migraines with auras group, SWI asymmetry was found in 26% (95% CI 18-35) compared to patients with migraines without auras (3%, [95% CI 1-8], < 0.001) and controls 7% [95% CI 3-14], < 0.001). There was no difference between patients with migraines without auras and controls ( = 0.19). The distinct SWI changes in migraines with and without auras suggest that CSD might not be involved in the pathophysiology of migraines without auras.